Antibacterial Activities Of Various Solvent Extracts From Impatiens Balsamina - S. AHMED JOHN,; M. KOPERUNCHOLAN, (International Journal of Pharma and Bio Sciences, 2012)
The antibacterial activities of Hexane, Petroleum ether, Acetone, Methanol, and Aqueous solution extracts from the plant “Impatiens balsamina” was screened against selective bacterial human pathogens namely Shigella boydii, Salmonella paratyphii, Proteus vulgaris, Staphylococcus aureus, Candida albicans and Cryptococcus neoformans by disc diffusion method. The bacterial pathogens Shigella boydii, Candida albicans, and Cryptrococcus neoformans showed good positive results (Susceptibility) to the plant extract of “Impatiens balsamina” that the zone of inhibition of bacterial pathogens were high in the scale of millimeter ranging from 16 mm to 38 mm. The pathogens Proteus vulgaris and Staphylococcus aureus shows moderate positive results (Susceptibility) to the plant extracts of “Impatiens balsamina” that the zone of inhibition of bacterial pathogens ranging from 1mm to 29 mm. From this above findings, we come to the conclusion that the plant “Impatiens balsamina” possesses certain phytochemical properties and these properties in the form of chemicals were responsible for the zone of inhibition formation on the bacterial growth. Therefore, it can be highly recommended for research in the process of drug development for several diseases